Halal labelization, word of mouth and halal awareness on purchase decisions of pharmaceutical products (case study of Yogyakarta muslim students) - Nur Aisyah Indarningsih; Siregar, Suci Wulandari (Journal of Halal Product and Research (JHPR), 2023)
Despite the importance of pharmaceutical products in everyday life, especially after the coronavirus outbreak in early 2020, only a few studies have attempted to analyze consumer behavior regarding halal pharmaceutical products. Therefore, this study aims to analyze the effect of halal labeling, word of mouth, and halal awareness on purchasing decisions for halal products among Yogyakarta Muslim students using the structural equation model (SEM). The sample for this research is 100 respondents spread across several campuses. Data collection was carried out online with the help of Google forms, which were distributed via social media on a Likert scale of 1–5. From the results of data processing, it was found that halal labeling, word of mouth, and halal awareness had a positive effect on purchasing decisions for pharmaceutical products. Halal awareness is the most significant determinant of purchasing decisions for halal pharmaceutical products, so the pharmaceutical industry needs to highlight the halal aspects of their products through proper branding and promotion/advertising campaigns. Halal aspects include the ingredients and substances of pharmaceutical products and the product manufacturing process. In addition to the halal aspect, aspects of product hygiene and safety need to be emphasized. In the post-COVID era, this is what Muslim consumers need.